(untitled) (IITM Journal of Business Studies, 2024)
Customer Expectation and Satisfaction have always been an engrossing and important topic of interest for the hospitality reseachers. It is important because it helps in understanding the needs of the customers and then generating and providing services accordingly. The purpose of this research paper is to provide the analytic data of the work that has been done in the field of customer expectation and satisfaction in hospitality industry. Using the keywords Hospitality and Customer Satsfaction a bibliometric analysis of 415 published research articles of 21st centaury. From the above mentioned research articles the most cited countries, authors, most referred articles and other parameters.